Touch screen silver paste and preparation method and application thereof

By using special-shaped silver powder, conductive carbon black and boron trichloride complex in touch screen silver paste, the particle size and morphology of silver powder are optimized, and the problems of poor conductivity and insufficient adhesion are solved, and high conductivity and low cost are achieved The effect is suitable for high-precision touch screen components.

CN119274845APending Publication Date: 2025-01-07NANTONG AISHENG NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411464523.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing touch screen paste has poor conductivity and poor adhesion, and is prone to bubbles during printing, resulting in poor electrical and mechanical properties, and the thin line width is difficult to reach within 80μm, affecting the laser engraving effect.

Method used

60 to 70 parts of special-shaped silver powder, 1 to 2 parts of conductive carbon black, 2 to 5 parts of additives and 26 to 35 parts of organic carrier, 1 to 2 parts of boron trichloride are added. Complex, silver paste is prepared by stirring and grinding, optimized the particle size and morphology of silver powder, and improved the conductive properties and adhesion of the slurry.

Benefits of technology

It achieves lower square and line resistance, improves conductivity, reduces silver content, simplifies printing technology, enhances adhesion and shapeshaping of silver paste, and is suitable for high-precision touch screen components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274845A_ABST
    Figure CN119274845A_ABST
Patent Text Reader

Abstract

The invention provides touch screen silver paste and a preparation method and application thereof, and belongs to the technical field of conductive paste. The touch screen silver paste comprises the following components in parts by mass: 60-70 parts of special-shaped silver powder; 1-2 parts by mass of conductive carbon black; 2-5 parts by mass of an auxiliary agent; 26-35 parts by mass of an organic carrier; and 1-2 parts by mass of a boron trichloride complex. By adopting the special-shaped silver powder, the line type of the paste can be improved, the thickness can be increased, and the line resistance and the sheet resistance can be continuously reduced, and meanwhile, the boron trichloride is added into the silver paste, so that the printing line type can be improved on the basis of ensuring the adhesive force level, the thickness can be further increased, and the line resistance and the sheet resistance can be further reduced; the conductive carbon black can also solve the problem of poor electrical performance caused by non-uniform filling of the silver powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive pastes, and in particular relates to a silver paste for a touch screen and a preparation method and application thereof. Background Art

[0002] Touch screens are widely used in high-end smart phones, laptops, digital cameras (GPS, imaging systems), PDAs, personal portable multimedia players (PMPs), etc. With the rapid development of these electronic products, higher requirements are placed on the functionality of key materials for touch screens.

[0003] Touch screen silver paste products are mainly made by rolling ultrafine silver powder, low-temperature curing thermoplastic resin, additives and organic solvents to a certain fineness through a three-roll grinder. They are high-silver content, low-temperature baking and fast curing silver pastes. They have excellent characteristics such as good printing performance, low resistance, good adhesion adaptability to different substrates, good laser cutting effect, and easy coating. They are mainly used in transparent conductive glass, ITO coating, organic glass and PET film in touch screens, and are suitable for production processes such as nano coating, fine line screen printing, capacitive screen laser cutting, and dispensing. In the production process, after the silver paste is printed on a certain mesh screen, the conductive particles are completely separated by organic polymers and organic solvents in the initial state, so the resistance is infinite. When baked under certain temperature conditions, the organic solvent evaporates and the film layer shrinks further. During the shrinkage process, the contact tightness between the conductive particles increases, the contact area increases, and the organic polymer is further filled into the holes, thereby increasing the density of the film layer and greatly improving the conductive performance. Therefore, the quality of touch screen silver paste products is directly related to its printability, conductive performance, adhesion, etc.

[0004] The conductive paste currently used in touch screens is usually conductive silver paste, in which the silver powder is mostly flaky powder, unevenly filled, and the formed silver paste has poor linearity, thin thickness, and poor conductivity. To ensure conductivity, the silver content of foreign silver paste is generally above 70%. Due to the high silver content, the cost is high. To save costs, the silver content of domestic silver paste is generally around 65%. Due to the reduced silver content, the paste has poor conductivity, poor adhesion, and bubbles are easily generated during the printing process, resulting in poor electrical and mechanical properties of the touch screen product after printing.

[0005] In addition, after the silver paste is printed on a polyester screen and cured in a baking oven at a certain time and temperature, it is laser engraved by a laser machine. Since the minimum fine line width is required to be 80μm for laser engraving, the coverage rate of the silver paste is relatively high. If the coverage rate is not enough, pinholes or dark breaks are likely to appear, which will cause adverse phenomena such as short circuits in the channels after laser engraving. However, if the coverage rate is increased too much, it will cause insufficient contact between the silver particles, and at the same time affect the physical properties such as electrical properties, and the silver paste process requirements are higher. At present, most of the silver paste fine lines on the market have a width of 50μm and a square resistance of 26mΩ / □. With the development of the information age, the demand for touch screen technology is also increasing. Just like the black frame of the screen of a smart phone, the narrower the fine line, the smaller the black frame of the screen can be, and even achieve a "borderless" effect. However, reducing the width of the silver paste fine line will require technological breakthroughs and innovations to achieve.

[0006] Therefore, it is necessary to optimize the components of touch screen silver paste and propose a new touch screen silver paste and its preparation method and application. Summary of the invention

[0007] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provide a touch screen silver paste and a preparation method and application thereof.

[0008] In one aspect of the present disclosure, a touch screen silver paste is provided, comprising:

[0009] 60-70 parts by weight of special-shaped silver powder;

[0010] 1 to 2 parts by mass of conductive carbon black;

[0011] 2 to 5 parts by weight of additives;

[0012] 26-35 parts by weight of an organic carrier;

[0013] 1 to 2 parts by mass of boron trichloride complex.

[0014] Optionally, the D50 particle size of the special-shaped silver powder is 0.8 to 1.2 μm, and the specific surface area is 1 to 1.3 m 2 / g, tap density is 3.8~4.3m 3 / g, and the burning loss is 0.4-0.5%.

[0015] Optionally, the special-shaped silver powder includes flaky silver powder and spherical silver powder; wherein,

[0016] The mass ratio of spherical silver powder to flake silver powder is (7-12):2.

[0017] Optionally, the spherical silver powder is an irregular polyhedron with a particle size of 0.3 to 1.5 μm;

[0018] The cross-sectional area perpendicular to the thickness direction of the flaky silver powder is an irregular circle, the particle size of the flaky silver powder is 1.6 to 2.5 μm, and the thickness is 0.01 to 0.5 μm.

[0019] Optionally, the D50 particle size of the conductive carbon black is 0.25-0.4 μm.

[0020] Optionally, the auxiliary agent includes one or more of a curing agent, a dispersant, an adhesion promoter, a coupling agent, a thickener, and a rheological agent.

[0021] Optionally, the organic carrier comprises:

[0022] 2 to 15 parts by weight of resin;

[0023] 70 to 95 parts by mass of solvent.

[0024] 0.5 to 5 parts by mass of auxiliary agents.

[0025] Another aspect of the present disclosure provides a method for preparing the aforementioned touch screen silver paste, the method comprising:

[0026] Obtaining an organic carrier;

[0027] The organic carrier is added into a disperser, and the special-shaped silver powder, the auxiliary agent, the conductive carbon black and the boron trichloride complex are added in sequence under stirring conditions, and the silver paste for the touch screen is obtained through stirring and grinding.

[0028] Optionally, the stirring rate is 500-800 r / min.

[0029] Another aspect of the present disclosure provides an application of silver paste for a touch screen, wherein the silver paste for a touch screen described above is applied to touch screen components.

[0030] Optionally, the application process includes:

[0031] The silver paste of the touch screen is printed on the substrate or slot filling of the touch screen components.

[0032] The present disclosure provides a touch screen silver paste and its preparation method and application, wherein the touch screen silver paste comprises: 60-70 parts by mass of special-shaped silver powder; 1-2 parts by mass of conductive carbon black; 2-5 parts by mass of additives; 26-35 parts by mass of organic carriers; and 1-2 parts by mass of boron trichloride complexes. The present disclosure uses special-shaped silver powder to improve the paste line shape, thicken the thickness, and further reduce the line resistance and square resistance. At the same time, by adding boron trichloride to the silver paste, the printing line shape can be improved on the basis of ensuring the adhesion level, so that the thickness is further increased, and the line resistance and square resistance are indirectly reduced. In addition, the conductive carbon black can also solve the problem of poor electrical performance caused by uneven filling of silver powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flowchart of a method for preparing silver paste for a touch screen according to an embodiment of the present invention. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0035] In one aspect of the present disclosure, a touch screen silver paste is provided, comprising: 60 to 70 parts by mass of special-shaped silver powder; 1 to 2 parts by mass of conductive carbon black; 2 to 5 parts by mass of an additive; 26 to 35 parts by mass of an organic carrier; and 1 to 2 parts by mass of a boron trichloride complex.

[0036] In this embodiment, by adding conductive carbon black to the silver paste, the problem of poor electrical properties caused by uneven contact of silver powder can be effectively solved, thereby improving the electrical conductivity. Secondly, the boron trichloride complex component can improve the printing line type on the basis of ensuring the adhesion level of the slurry, make the thickness thicker, and indirectly reduce the line resistance and square resistance. Furthermore, by using special-shaped silver powder, the slurry line type can be further improved, the thickness is further thickened, the line resistance and square resistance continue to decrease, and the electrical conductivity is further improved. In summary, the silver paste formed based on the above-mentioned components has lower square resistance and line resistance, thereby improving electrical conductivity, without the need for a large amount of silver content, and, in actual application, it can be directly printed on the surface of the substrate to form a conductive circuit without the need for complex processes.

[0037] It should be noted that the content and form (flake, spherical), particle size distribution, loose tap density, and microscopic contact state during film formation of the silver powder all have a great influence on the performance of the slurry. In view of this, the present embodiment uses special-shaped silver powder to help improve the linear shape of the slurry and increase the thickness.

[0038] In some preferred embodiments, the content of the special-shaped silver powder may be preferably 60 parts by mass, 63 parts by mass, 65 parts by mass, 67 parts by mass, etc., and its D50 particle size is preferably 0.8 to 1.2 μm.

[0039] For example, 0.8μm, 0.9μm, 1.0m, 1.1μm, 1.2μm, etc.; the specific surface area is 1 to 1.3m 2 / g,

[0040] For example, 1m 2 / g, 1.1m2 / g, 1.2m 2 / g, 1.3m 2 / g, etc.; the tap density is 3.8~4.3m 3 / g, for example, 3.8m 3 / g, 4.0m 3 / g, 4.1m 3 / g, 4.2m 3 / g, 4.3m 3 / g, etc.; the burning loss is 0.4-0.5%, for example, 0.42%, 0.45%, 0.47%, 0.5%, etc.

[0041] The special-shaped silver powder of this embodiment can be prepared by chemical synthesis.

[0042] In other preferred embodiments, the special-shaped silver powder includes flake silver powder and spherical silver powder; wherein the mass ratio of the spherical silver powder to the flake silver powder is (7-12):2, for example, 7:2, 8:2, 10:2, 11:2, 12:2, etc.

[0043] As a further preferred embodiment, the particle size of the flaky silver powder is in the range of 1.6 to 2.5 μm, the average particle size is preferably 1.8 to 2.2 μm, for example, 1.8 μm, 2.0 μm, 2.2 μm, etc., and the thickness is preferably 0.01 to 0.5 μm, for example, 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, etc. In addition, the morphology of the flaky silver powder is preferably irregularly circular, that is, the overall shape of the flaky silver powder is similar to a disc, but the edge is not smooth and flat, but has a straight, uneven or arc-shaped edge, and the cross-sectional area perpendicular to the thickness direction of the flaky silver powder is irregularly circular, forming an irregular disc-like structure.

[0044] As a further preferred embodiment, the particle size of the spherical silver powder is 0.3-1.5 μm, the average particle size is 0.5-1.2 μm, and the average particle size is 0.5-1.2 μm, for example, 0.5 μm, 0.7 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, etc. In addition, the spherical silver powder is an irregular polyhedron, that is, the spherical silver powder is not a normal spherical structure, but an irregular spherical-like structure.

[0045] It should be further explained that, in order to further improve the electrical properties and plasticity of the silver paste, in some preferred embodiments, other components are further optimized, for example, conductive carbon black and boron trichloride complex are added.

[0046] In some preferred embodiments, the content of conductive carbon black may be preferably 1 mass part, 1.2 mass parts, 1.5 mass parts, 1.7 mass parts, 2 mass parts, etc., and its D50 particle size is preferably 0.25-0.4 μm, for example, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, etc., and can be prepared by mechanical ball milling.

[0047] In other preferred embodiments, the content of the auxiliary agent may preferably be 2 parts by mass, 3 parts by mass, 4 parts by mass, 5 parts by mass, etc., and the auxiliary agent includes one or more of a curing agent, a dispersant, an adhesion promoter, a coupling agent, a thickener, and a rheological agent.

[0048] As a further preferred solution, the curing agent includes one or more of isocyanates, imidazoles, and cationic agents, which are used to enhance the hardness, wear resistance, and service life of the conductive paste.

[0049] As a further preferred embodiment, the dispersant includes one or more of an organic dispersant, an inorganic dispersant, a chelating agent, and a polymer dispersant, which are used to prevent particles from reaggregating and precipitating and improve the fluidity and stability of the conductive paste.

[0050] As a further preferred embodiment, the adhesion promoter includes one or more of silanes, phenolic resins, composites, and functional silicas, which are used to reduce interfacial tension, enhance intermolecular interactions, and increase the bonding strength between the conductive paste and the substrate, thereby enhancing the adhesion and durability of the conductive paste.

[0051] As a further preferred embodiment, the coupling agent includes one or more of silanes, phthalates, and phosphates, which are used to improve the dispersibility of the conductive filler, enhance the interaction between the conductive particles and the matrix, and improve the dispersibility of the conductive paste.

[0052] As a further preferred embodiment, the thickener includes one or more of organic bentonite, silica, castor oil, and polyamide wax, which are used to increase the viscosity and plasticity of the slurry, enhance its fluidity and adhesion, and thus improve the conductivity and durability.

[0053] As a further preferred embodiment, the rheological agent includes one or more of an inorganic system, an organic system, a special functional system, and an aqueous system, which is used to improve the fluidity and stability of the slurry, improve the coating or printing efficiency, and thus improve the coating quality.

[0054] In other preferred embodiments, the content of the organic carrier may be preferably 26 parts by mass, 28 parts by mass, 30 parts by mass, 33 parts by mass, 35 parts by mass, etc. The organic carrier includes: a resin, a solvent and an additive.

[0055] As a further preferred embodiment, in the organic carrier, the content of the resin may be preferably 2 to 15 parts by mass, for example, 2 parts by mass, 5 parts by mass, 7 parts by mass, 10 parts by mass, 12 parts by mass, 15 parts by mass, etc., and more preferably 2 to 10 parts by mass. Secondly, the resin may preferably be one or more of epoxy resin, saturated polyester resin, polyurethane resin, chloroacetic resin, acrylic resin, epoxy modified resin, and modified silicone resin. Of course, in other preferred embodiments, resins of other contents and other types of resins may also be selected, and this is not specifically limited.

[0056] As a further preferred embodiment, in the organic vehicle, the content of the solvent may be preferably 70 to 95 parts by mass, for example, 70 parts by mass, 75 parts by mass, 80 parts by mass, 90 parts by mass, 95 parts by mass, etc., and more preferably 70 to 90 parts by mass. Secondly, the solvent may be preferably one or more of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, and dibasic acid ester.

[0057] As a further preferred embodiment, in the organic carrier, the content of the auxiliary agent can be preferably 0.5 to 5 parts by mass, for example, 1 part by mass, 1.5 parts by mass, 2 parts by mass, 2.5 parts by mass, 3 parts by mass, 4 parts by mass, 5 parts by mass, etc., and more preferably 1 to 3 parts by mass. Secondly, the auxiliary agent can be preferably a coupling agent, a leveling agent, etc.; wherein the coupling agent can be one or more of silane, phthalate, and phosphate, and the rheological agent can be one or more of an inorganic system, an organic system, a special functional system, and an aqueous system, and there is no specific limitation on this, and it can be selected according to actual needs.

[0058] Furthermore, the content of the boron trichloride complex may preferably be 1 part by mass, 1.2 parts by mass, 1.5 parts by mass, 1.7 parts by mass, 2.0 parts by mass, etc. This component can improve the printing line type of the slurry, increase the thickness, and further reduce the line resistance and square resistance.

[0059] In this embodiment, based on the use of special-shaped silver powder, and by adding conductive carbon black and boron trichloride complex and other components to the silver paste, when the silver powder content is a low silver content of 60-70%, the paste can still ensure good conductivity, and at the same time can make the paste have good adhesion, and on the basis of ensuring the adhesion level, can improve the printing line type, increase the printing thickness, and further reduce the line resistance and square resistance.

[0060] The silver paste of this embodiment has a viscosity range of 180-200 dpa·s, an adhesion of 5B grade, a thickness of 4.5-5 μm, preferably 5 μm, a line resistance of 132-157 Ω, and a square resistance of 7.79-8.34 Ω. Compared with conventional silver paste currently used in touch screens, the silver paste has a thicker thickness, lower line resistance and square resistance, and better conductivity, while effectively reducing the silver content and reducing costs.

[0061] like Figure 1 As shown, another aspect of the present disclosure provides a method S110 for preparing the silver paste for a touch screen as described above, comprising the following specific steps S110 to S120:

[0062] S110, obtaining an organic carrier.

[0063] Specifically, 2 to 15 parts by mass of a resin, 70 to 95 parts by mass of a solvent, and 1 to 3 parts by mass of an auxiliary agent are mixed and stirred uniformly using a disperser to obtain an organic vehicle.

[0064] It should be noted that the specific components of the resin, solvent and auxiliary agent of this embodiment can be referred to the above description and are not specifically limited here.

[0065] S120, adding an organic carrier into a disperser, and sequentially adding special-shaped silver powder, an additive, conductive carbon black, and a boron trichloride complex under stirring conditions, stirring evenly, and grinding to obtain a touch screen silver paste.

[0066] Specifically, 26 to 35 parts by mass of the organic carrier obtained in step S110 are added to a planetary disperser, and under a stirring condition of 500 to 800 r / min, 60 to 70 parts by mass of special-shaped silver powder, 2 to 5 parts by mass of an auxiliary agent, 1 to 2 parts by mass of a conductive carbon black, and 1 to 2 parts by mass of a boron trichloride complex are added in sequence. After stirring evenly, the mixture is transferred to a three-roll mill or a sand mill and ground to a fineness of less than 5 um to obtain a touch screen silver paste.

[0067] It should be noted that the specific parameters of the special-shaped silver powder, additives and conductive carbon black in this embodiment can be referred to the above description and are not specifically limited here.

[0068] The preparation method of this embodiment is simple, and by optimizing the components and their contents, the printed line type of the conductive paste can be improved, the thickness can be increased, and the line resistance and square resistance can be reduced.

[0069] Another aspect of the present disclosure provides an application of silver paste for a touch screen, wherein the silver paste for a touch screen provided above is applied to touch screen components.

[0070] In some preferred embodiments, the touch screen silver paste is applied to the touch screens of electronic products such as medical education, shopping mall touch displays, tablets, mobile phones, etc.

[0071] The touch screen silver paste proposed in this embodiment is mainly used on substrates such as transparent conductive glass, ITO coating, organic glass and PET film in the touch screen. The silver paste is directly coated on the surface of the substrate through a precise printing process to form a fine conductive circuit, which can provide good conductivity and touch sensitivity for the touch screen.

[0072] It is worth noting that in the actual application process, because the touch screen silver paste in the present application has excellent plasticity and adhesion, the touch screen silver paste of the preferred embodiment can be directly formed on the substrate of the touch screen components by screen printing, without filling in the groove, so as to improve the electrical performance by improving the line shape. Of course, in some embodiments, it can also be filled in the groove of the substrate to form electrodes and circuits, such as forming a metal grid, which is not easy to collapse or fall off and has better adhesion than the current ordinary slot filling silver paste.

[0073] The following will further illustrate the touch screen silver paste and preparation method in conjunction with specific examples:

[0074] Example 1

[0075] The silver paste of this example includes: 63 parts by mass of special-shaped silver powder, 1.5 parts by mass of conductive carbon black, 3 parts by mass of additives, 31.3 parts by mass of organic carrier and 1.2 parts by mass of boron trichloride complex. Please refer to Table 1 for the specific composition and content.

[0076] (1) In the special-shaped silver powder, the mass ratio of spherical silver powder to flake silver powder is 8:2; the particle size of the spherical silver powder is 0.4-1.3 μm, and the average particle size is 0.8 μm; the particle size of the flake silver powder is 1.8-2.1 μm, and the average particle size is 2.0 μm; the thickness of the flake silver powder is 0.05-0.2 μm, and the average thickness is 0.11 μm; the D50 particle size of the special-shaped silver powder as a whole is 1.05 μm, and the specific surface area is 1.18 m 2 / g, tap density is 4.18m 3 / g, and the loss on ignition is 0.46%.

[0077] (2) The additives include: isocyanate curing agent: acrylate dispersant: modified polysiloxane (adhesion promoter): tetraethyl titanate (coupling agent): organic bentonite (thickener): hydrogenated castor oil (rheological agent) in a mass ratio of 1.5:1.2:1:1:0.5:0.5.

[0078] (3) The particle size of conductive carbon black D50 is 0.33 μm.

[0079] (4) The organic carrier includes the following components in parts by weight: 10 parts by weight of resin, 88 parts by weight of solvent, and 2 parts by weight of auxiliary agent. Among them, the resin is a mixed resin of saturated polyester resin, chloroacetic acid resin and polyurethane resin, and the mass ratio of polyester resin, chloroacetic acid resin and polyurethane resin is 2:1:1. The solvent is a mixed solvent of diethylene glycol ethyl ether acetate and dibasic acid ester. The mass ratio of diethylene glycol ethyl ether acetate to dibasic acid ester is 3:1. The auxiliary agent is a silane coupling agent and a hydrogenated castor oil rheological agent, and the mass ratio is 1:1.

[0080] The silver paste of Example 1 was printed on a substrate, and its performance was tested. The results are shown in Table 2. Its viscosity was 190 dPa·s, the adhesion could reach 5B grade, the thickness was 5 μm, the line resistance was 132Ω, and the square resistance was 7.79 mΩ / □ / mill.

[0081] Example 2

[0082] The silver paste of this example includes: 63 parts by mass of special-shaped silver powder, 1.5 parts by mass of conductive carbon black, 3 parts by mass of additives, 31 parts by mass of organic carrier and 1.5 parts by mass of boron trichloride complex. Please refer to Table 1 for the specific composition and content.

[0083] In this embodiment 2, the special-shaped silver powder, conductive carbon black, additives, organic carrier and boron trichloride complex used are the same as those in embodiment 1.

[0084] The silver paste of Example 2 was printed on a substrate, and its performance was tested. The results are shown in Table 2. Its viscosity was 200 dpa·s, the adhesion could reach 5B grade, the thickness was 4.5 μm, the line resistance was 157 Ω, and the square resistance was 8.34 mΩ / □ / mill.

[0085] Example 3

[0086] The silver paste of this example includes: 63 parts by mass of special-shaped silver powder, 1.5 parts by mass of conductive carbon black, 3 parts by mass of additives, 30.5 parts by mass of organic carrier and 2 parts by mass of boron trichloride complex. Please refer to Table 1 for the specific composition and content.

[0087] In this embodiment 3, the special-shaped silver powder, conductive carbon black, additives, organic carrier and boron trichloride complex used are the same as those in embodiment 1.

[0088] The silver paste of Example 3 was printed on a substrate, and its performance was tested. The results are shown in Table 2. Its viscosity was 180 dPa·s, the adhesion could reach 5B grade, the thickness was 5 μm, the line resistance was 141 Ω, and the square resistance was 8.32 mΩ / □ / mill.

[0089] Table 1 Components of silver paste of Examples 1-3

[0090]

[0091] Table 2 Performance of silver paste in Examples 1-3

[0092]

[0093] Comparative Example 1

[0094] The silver paste of this comparative example comprises: 63 parts by mass of spherical silver powder, 1.5 parts by mass of conductive carbon black, 3 parts by mass of an auxiliary agent, 31.3 parts by mass of an organic carrier and 1.2 parts by mass of a boron trichloride complex.

[0095] In this comparative example 1, the spherical silver powder used has a D50 particle size of 1.05 μm and is a regular spherical silver powder. The conductive carbon black, additive, organic carrier and boron trichloride complex are the same as those in Example 1.

[0096] The silver paste of comparative example 1 was printed on a substrate, and its performance was tested. The results are shown in Table 3. Its viscosity was 150 dpa·s, the adhesion could reach 5B grade, the thickness was 3 μm, the line resistance was 292Ω, and the square resistance was 11.3 mΩ / □ / mill.

[0097] Compared with Examples 1-3, the single ball powder has low viscosity, uneven dispersion, large line resistance and square resistance, and poor electrical performance. This shows that by using special-shaped silver powder, the dispersion of the slurry can be improved, the line shape can be further improved, and the thickness can be further increased, and the line resistance and square resistance can be further reduced.

[0098] Comparative Example 2

[0099] The silver paste of this comparative example comprises: 63 parts by mass of special-shaped silver powder, 1.5 parts by mass of conductive carbon black, 3 parts by mass of additives, and 32.5 parts by mass of an organic carrier.

[0100] In this comparative example 2, the special-shaped silver powder, conductive carbon black, additives, and organic carrier used are the same as those in Example 1.

[0101] The silver paste of comparative example 2 was printed on a substrate, and its performance was tested. The results are shown in Table 3. Its viscosity was 170 dpa·s, the adhesion could reach 5B grade, the thickness was 5 μm, the line resistance was 308Ω, and the square resistance was 14.6 mΩ / □ / mill.

[0102] Compared with Examples 1-3, the silver paste formed without adding boron trifluoride complex has lower viscosity, larger line resistance and square resistance, and poor conductivity. This shows that by adding boron trichloride, the printing line type can be improved and the thickness can be increased while ensuring the adhesion level, thereby indirectly reducing the line resistance and square resistance.

[0103] Comparative Example 3

[0104] The silver paste of this comparative example includes: 63 parts by mass of special-shaped silver powder, 1.5 parts by mass of conductive carbon black, 3 parts by mass of additives, 31.3 parts by mass of organic carrier and 1.2 parts by mass of silicone oil.

[0105] In this comparative example 3, the special-shaped silver powder, conductive carbon black, additives, and organic carrier used are the same as those in Example 1.

[0106] The silver paste of comparative example 3 was printed on a substrate, and its performance was tested. The results are shown in Table 3. Its viscosity was 180 dPa·s, the adhesion could reach 5B grade, the thickness was 4 μm, the line resistance was 245Ω, and the square resistance was 11.8 mΩ / □ / mill.

[0107] Table 3 Performance of silver paste in comparative examples 1-3

[0108]

[0109] Compared with Examples 1-3 and Comparative Example 2, it can be seen that although silicone oil can reduce line resistance and square resistance to a certain extent, its thickness is still relatively thin, which further illustrates that adding boron trichloride can improve the printing line type and make the thickness thicker while ensuring the adhesion level, thereby indirectly reducing line resistance and square resistance.

[0110] The present disclosure provides a touch screen silver paste and a preparation method and application thereof, which have the following beneficial effects compared with the prior art:

[0111] First, the use of special-shaped silver powder in the present disclosure can improve the line shape, increase the printing thickness, reduce the line resistance and square resistance, increase the conductivity, and reduce the silver content;

[0112] Second, the present disclosure can improve the printing line type of the paste and make the thickness thicker while ensuring the adhesion level by adding the boron trichloride complex to the silver paste, thereby indirectly reducing the line resistance and square resistance;

[0113] Third, the present disclosure can solve the problem of reduced electrical performance caused by uneven contact of silver powder by adding conductive carbon black to the silver paste, and effectively improve the conductive performance;

[0114] Fourth, the silver paste disclosed in the present invention can be directly printed on the surface of the substrate in practical applications, the process is simple, and has good linearity and adhesion, and is relatively thick.

[0115] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A touch screen silver paste, characterized in that: include: 60-70 parts by weight of special-shaped silver powder; 1 to 2 parts by mass of conductive carbon black; 2 to 5 parts by weight of additives; 26-35 parts by weight of an organic carrier; 1 to 2 parts by mass of boron trichloride complex.

2. The touch screen silver paste according to claim 1, characterized in that: The D50 particle size of the special-shaped silver powder is 0.8-1.2 μm, and the specific surface area is 1-1.3 m 2 / g, tap density is 3.8~4.3m 3 / g, and the burning loss is 0.4-0.5%.

3. The touch screen silver paste according to claim 1, characterized in that: The special-shaped silver powder includes flaky silver powder and spherical silver powder; wherein, The mass ratio of spherical silver powder to flake silver powder is (7-12):

2.

4. The touch screen silver paste according to claim 3, characterized in that: The spherical silver powder is an irregular polyhedron with a particle size of 0.3 to 1.5 μm; The cross-sectional area perpendicular to the thickness direction of the flaky silver powder is an irregular circle, the particle size of the flaky silver powder is 1.6 to 2.5 μm, and the thickness is 0.01 to 0.5 μm.

5. The touch screen silver paste according to any one of claims 1 to 4, characterized in that: The D50 particle size of the conductive carbon black is 0.25 to 0.4 μm.

6. The touch screen silver paste according to any one of claims 1 to 4, characterized in that: The auxiliary agent includes one or more of a curing agent, a dispersant, an adhesion promoter, a coupling agent, a thickener, and a rheological agent.

7. The touch screen silver paste according to any one of claims 1 to 4, characterized in that: The organic carrier comprises: 2 to 15 parts by weight of resin; 70 to 95 parts by mass of a solvent; 0.5 to 5 parts by mass of auxiliary agents.

8. A method for preparing the silver paste for a touch screen according to any one of claims 1 to 7, characterized in that: The method comprises: Obtaining an organic carrier; The organic carrier is added into a disperser, and the special-shaped silver powder, the auxiliary agent, the conductive carbon black and the boron trichloride complex are added in sequence under stirring conditions, and the silver paste for the touch screen is obtained through stirring and grinding.

9. An application of silver paste for a touch screen, characterized in that: The touch screen silver paste according to any one of claims 1 to 7 is applied to touch screen components.

10. The use according to claim 9, characterized in that: The application process includes: The touch screen silver paste is printed on a substrate or a slot filling device of a touch screen component.